The Effect of Income Diversification on Default Risk in Conventional Banking Companies in Indonesia - Tambunan, Alexandria Leonard; Indriyantini, Dhiya Faza; Puspita, Grace Febiola; Lestari, Henny Setyo (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2024)
This study aims to identify variables that affect the risk of bankruptcy in banks listed on the Indonesia Stock Exchange. The research method includes collecting data from 36 listed banks on the Indonesia Stock Exchange over a 5-year period (2018-2022) and using the panel data regression analysis method. The addition of novelty variables in this study, namely bank size, net interest margin, and deposit to total assets that have a negative effect on bankruptcy risk, while the diversification index and gross domestic product variables have no effect on bankruptcy risk. the implication for bank managers is as a reference and consideration in implementing income diversification strategies. this research also provides information that is expected to be used as reference material and expand information and insight in developing research in the banking sector.